SATISFACTION WITH THE STUDY AMONG STUDENTS WITH DIFFERENT LEVEL OF SOCIAL ORIENTATIONS OF SELF. THE ROLE OF EXPERIENCE GAINED IN COLLEGE - STOJANOWSKA, ELŻBIETA; BAJ, MARIUSZ (Studia Psychologica: Theoria et praxis, 2016)
Research carried outin a group of first years students of study (N = 302) concerned the importance of social orientation of self (according to the concept of Singelis, Triandis and co-workers) and experience gained in college in the areas corresponding to these orientations for the satisfaction of the study. The results showed that in the research group horizontal orientations dominated vertical. The important determinants of satisfaction with studies bothin womenand menwere positive experiencein the field of horizontal collectivism (supporting peer relationships) and horizontal individualism (autonomy), but immediately those orientations were not determined the satisfaction. Vertical orientations and experience related to them were irrelevant for satisfaction in women, while in men the orientation of vertical individualism disrupted (weakly) the achievement of satisfaction.